A four-part working bibliography of neuroethics: part 2 – neuroscientific studies of morality and ethics - Darragh, Martina (Philos Ethics Humanit Med, 2015)
BACKGROUND: Moral philosophy and psychology have sought to define the nature of right and wrong, and good and evil. The industrial turn of the twentieth century fostered increasingly technological approaches that conjoined philosophy to psychology, and psychology to the natural sciences. Thus, moral philosophy and psychology became ever more vested to investigations of the anatomic structures and physiologic processes involved in cognition, emotion and behavior - ultimately falling under the rubric of the neurosciences. Since 2002, neuroscientific studies of moral thought, emotions and behaviors have become known as – and a part of – the relatively new discipline of neuroethics. Herein we present Part 2 of a bibliography of neuroethics from 2002–2013 addressing the “neuroscience of ethics” – studies of putative neural substrates and mechanisms involved in cognitive, emotional and behavioral processes of morality and ethics. METHODS: A systematic survey of the neuroethics literature was undertaken. Bibliographic searches were performed by accessing 11 databases, 8 literature depositories, and 4 individual journal searches, and employed indexing language for National Library of Medicine (NLM) Medical Subject Heading databases. All bibliographic searches were conducted using the RefWorks citation management program. RESULTS: This bibliography lists 397 articles, 65 books, and 52 book chapters that present (1) empirical/experimental studies, overviews, and reviews of neural substrates and mechanisms involved in morality and ethics, and/or (2) reflections upon such studies and their implications. These works present resources offering iterative descriptions, definitions and criticisms of neural processes involved in moral cognition and behaviors, and also provide a historical view of this field, and insights to its developing canon.